Implementasi Healthy Building Berbasis Internet of Things pada Taman Kanak-kanak Al Baraakah, RA Kreatif - Kusumaningrum, Evy; Sumarsono, Sumarsono; Setiawan, Chanief Budi; Hariyadi, Dedy (Computer Science and Information Technology, 2024)
The limited availability of air quality sensors leads to potential exposure to pollution that poses health risks. Monitoring of crucial clean air indicators, such as ISPU standards and emission requirements, as well as management of important aspects of healthy buildings such as ventilation, temperature, humidity, and security, are also inadequate. As a solution, this article proposes the development of an Internet of Things (IoT)-based smart school that utilizes advanced sensor technology to monitor and manage the condition of the educational environment in accordance with the healthy building foundation proposed by the Harvard T.H. Chan School of Public Health. With the integration of Tuya-based sensors and the use of HomeAssistant platform for automation, the implementation of this system in educational institutions such as TK Al Baraakah, RA Kreatif successfully created a healthier environment. As a result, better building conditions are achieved through real-time monitoring of vital parameters, forming a structured approach to creating safer and more comfortable schools for students and faculty. Monitoring and management can be shown on the Dashboard of the HomeAssistant platform.